Fate of copper in intensive shrimp farms: bioaccumulation and deposition in pond sediments - LD. Lacerda (Brazilian Journal of Biology)
We present the distribution of Cu in water, sediments and biomass from intensive shrimp (Litopenaeus vannamei Boone, 1931)) farming in northeastern Brazil. The results show no difference in dissolved Cu concentrations between waters entering and leaving the ponds. However, there was a large export of particulate Cu to adjacent environments, showed by extremely high particulate (112 µg.L-1) Cu concentrations in draining waters. Copper concentrations in the bottom sediments of the pond varied with depth from 10 to 20 µg.g-1, being 5 to 7 times higher than the local background. Pond management procedures result in a peculiar vertical distribution of Cu with peak values occurring at sub-surface depths in pond bottom sediments. Bioavailable Cu reaches about 20% of the total Cu content in sediments. Notwithstanding the relatively high Cu bioavailability, concentrations in shrimp muscle (23.2 to 63.4 µg.g-1 d.w.) were similar to reported values for reared and natural L. vannamei populations, and much lower than acceptable maximum limits for human consumption. Concentrations in the exoskeleton were always higher than in muscle. Increasing Cu mass, and to a lesser extent Cu concentrations in muscle tissues, occurred simultaneously to a decrease in Cu mass and concentrations in the exoskeleton and vice versa, suggesting a dynamical exchange of Cu between the two compartments. Although Cu fate in intensive shrimp culture does not result in increasing Cu exposure to consumers, the activity is an important source of this metal to adjacent ecosystems, in particular in the pristine environments where most aquaculture activities in NE Brazil takes place.